A single-set functional training program increases muscle power, improves functional fitness, and reduces pro-inflammatory cytokines in postmenopausal women: A randomized clinical trial - Rocha, Jackson Neris de Souza; Vasconcelos, Alan Bruno Silva; Aragão-Santos, José Carlos; de Resende–Neto, Antônio Gomes; Monteiro, Marcos Raphael Pereira; Nogueira, Albernon Costa; Cardoso, Alan Pantoja; Corrêa, Cristiane Bani; Moura, Tatiana Rodrigues de; Da Silva-Grigoletto, Marzo Edir (Frontiers in Physiology, 2023)
Aging can be associated with reduced muscle power, functional decline, and increased plasma concentrations of proinflammatory cytokines. Functional training (FT) can improve muscle power, functional fitness and reduce plasma cytokines. However, the FT optimal volume required to produce these adaptations must be clarified. Our study analyzed the effects of multiple-set functional training (MSFT) and single-set functional training (SSFT) on postmenopausal women's muscle power, functional fitness, and inflammatory profile. Forty-three women were randomly allocated into three groups: MSFT (n=16, age 64.13 ± 5.17), SSFT (n=14, age 63.79 ± 4.88), and control group (CG, n=13, age 64.62 ± 5.44). The bench press and squat exercises evaluated upper and lower limb muscle power. The following tests assessed functional fitness: putting on and taking off a T-shirt, gallon-jug shelf-transfer, standing up and walking around the house, five times sit-to-stand, and,400-meter walk. Plasma cytokine (TNF-α, IL-6, and IL-10) concentrations were measured by flow cytometry. SSFT and MSFT increased upper and lower limbs muscle power and improved functional fitness, except for the putting on and taking off a T-shirt test. MSFT reduced TNF-α and IL-6, while SSFT reduced only TNF-α. IL-10 was unaffected by exercise. SSFT and MSFT, therefore, promoted similar muscle power and functional fitness improvements over 24 weeks. MSFT was more effective than SSFT, reducing both TNF and IL-6, while SSFT only decreased TNF-α.